The Influence of Organizational Justice on Turnover Intention of Employees in Food and Beverage Industry in Nigeria - Chukwu, B.A. (International Journal of Economics, Business and Management Studies, 2019)
This research explored the influence of organizational justice on employee turnover intention. Labour turnover has negative impact on food and beverage industry in Nigeria in form of direct and indirect cost. Labour turnover is a source of economic drain to the food and beverage industry in Nigeria. Retention of employee is not easy and is a complex issue. Management of food and beverage industry can reduce turnover by considering different preventive measures such as entrenchment of Justice in organization especially where it concerns distribution of reward and treatment of staff. Employees will opt out of the organization if denied Justice in organization. This study adopted a Survey research design through administration of questionnaire to sampled firms. The data for the research was analyzed using descriptive statistics and Chi-square. The empirical result from the Chi-square analysis showed that fairness in procedure and process of getting reward, fairness in distribution of outcomes such as reward, fairness in personal treatment of employees received from authority figures and entrenchment of Justice in organization has significant influence on employee turnover intention at 5percent level of significance. Based on the findings of this research, it is recommended that there should be fairness in procedure and process of getting and distributing reward in organization. And that Justice should be entrenched in organizational Culture.